2018
DOI: 10.14444/5081
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive, Stereotactic, Wireless, Percutaneous Pedicle Screw Placement in the Lumbar Spine: Accuracy Rates With 182 Consecutive Screws

Abstract: Background: Standard fluoroscopic navigation and stereotactic computed tomography-guided lumbar pedicle screw instrumentation traditionally relied on the placement of Kirshner wires (K-wires) to ensure accurate screw placement. The use of K-wires, however, is associated with a risk of morbidity due to potential ventral displacement into the retroperitoneum. We report our experience using a computer image-guided, wireless method for pedicle screw placement. We hypothesize that minimally invasive, wireless pedic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 58 publications
3
8
0
Order By: Relevance
“…4). The present clinical accuracy rates compare favorably with literature reporting percutaneous pedicle screw insertion accuracy rates for manual computer-navigated methods (range 96%-100%), 6,7,[23][24][25][26][27][28]40 particularly for the lower reported thoracic insertion accuracies ranging from 75.6% to 94.9%, where the anatomical threshold for error is smaller. 6,25 The present results also compare favorably with robot-navigated percutaneous insertion, where reported clinical accuracy rates range widely from 89% to 100%, depending on the timing of publication and robot platform used.…”
Section: Discussionsupporting
confidence: 82%
“…4). The present clinical accuracy rates compare favorably with literature reporting percutaneous pedicle screw insertion accuracy rates for manual computer-navigated methods (range 96%-100%), 6,7,[23][24][25][26][27][28]40 particularly for the lower reported thoracic insertion accuracies ranging from 75.6% to 94.9%, where the anatomical threshold for error is smaller. 6,25 The present results also compare favorably with robot-navigated percutaneous insertion, where reported clinical accuracy rates range widely from 89% to 100%, depending on the timing of publication and robot platform used.…”
Section: Discussionsupporting
confidence: 82%
“…Van et al evaluated 1922 screws in an international, multicenter study and found 97.5% correct placements and 1.8% needing immediate revision. Sadrameli et al (2018) conducted wireless percutaneous pedicle screw placement for 182 screws and demonstrated 90.1% screw accuracy [22]. Higher than in previous reports, the present study showed 99.66% accuracy.…”
Section: Discussionsupporting
confidence: 46%
“…At this point, percutaneous rods are placed and any indicated compressions, distractions, and/or reductions are performed. A second fluoroscopy scan is taken to confirm accurate screw placement prior to the tightening of locking caps [11]. Subsequently, a 3D fluoroscopy scan is taken as an additional confirmation of accuracy.…”
Section: Percutaneous Pedicle Screws: Wiltse Approachmentioning
confidence: 99%